The Value of Cranial CT Imaging in Patients With Headache at the Emergency Department - Lemmens, Cynthia M. C.; van der Linden, M. Christien; Jellema, Korné (Frontiers in Neurology, 2021)
Background: Headache is among the most prevalent complaints in patients presenting to the emergency department (ED). Clinicians are faced with the difficult task to differentiate primary (benign) from secondary headache disorders, since no international guidelines currently exist of clinical indicators for neuroimaging in headache patients. Methods: We performed a retrospective review of 501 patients who presented at the ED with headache as a primary complaint between April 2018 and December 2018. Primary outcomes included the amount of diagnostic imaging, the different conclusions provided by diagnostic imaging, and the clinical factors associated with abnormal imaging results. Results: About half of the patients were diagnosed with a primary headache disorder. Cranial CT imaging at the ED was performed regularly (61% of the patients) and led to the diagnosis of underlying pathology in 1 in 7.6 patients. In a multivariate model, factors significantly associated with abnormal cranial CT results were age 50 years or older, presentation within 1 h after headache onset, clinical history of aphasia, and focal neurological deficit at examination. Conclusions: As separate clinical characteristics have limited value in detecting severe underlying headache disorders, cranial imaging is regularly performed in the ED. Clinical prediction model tools applied to headache patients may identify patients at risk of intracranial pathology prior to diagnostic imaging and reduce cranial imaging in the future.